Isolation of the Tumor-Inducing RNA from Oncogenic and Nononcogenic Agrobacterium tumefaciens - Beljanski, M. (1974)
Two RNA fractions have been isolated and purified from both oncogenic and nononcogenic strains of Agrobacterium tumefaciens. Both RNAs are capable of inducing the formation of transplantable tumors when introduced at wound sites in stems of Datura stramonium plants. One of these RNA fractions was found to be bound to an RNA-directed DNA polymerase, while the other was associated with the bacterial DNA. Physical evidence suggests that both are single stranded and small in size; linear sucrose gradients show that their size corresponds to a value of 5-6 S. A concentration of 4-5 μg of the RNAs dissolved in 0.01 ml of water is effective in initiating the formation of transplantable tumors in Datura plants.